The Berenstain Bears and the golden rule - Berenstain, Mike, 1951-; Berenstain, Stan, 1923-2005.; Berenstain, Jan, 1923-2012. (Grand Rapids, Mich. : Zonderkidz, 2008)
Sister Bear learns the true meaning of the golden rule that is engraved in her locket when a new bear arrives at school and no one invites her to play.
Keywords: Golden rule -- Fiction; Friendship -- Fiction; Schools -- Fiction; Bears -- Fiction; Christian life -- Fiction